2016
DOI: 10.1186/s41038-016-0055-7
|View full text |Cite
|
Sign up to set email alerts
|

Partial epithelial-mesenchymal transition in keloid scars: regulation of keloid keratinocyte gene expression by transforming growth factor-β1

Abstract: BackgroundKeloids are an extreme form of abnormal scarring that result from a pathological fibroproliferative wound healing process. The molecular mechanisms driving keloid pathology remain incompletely understood, hindering development of targeted, effective therapies. Recent studies in our laboratory demonstrated that keloid keratinocytes exhibit adhesion abnormalities and display a transcriptional signature reminiscent of cells undergoing epithelial-mesenchymal transition (EMT), suggesting a role for EMT in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
72
0
5

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(82 citation statements)
references
References 89 publications
(135 reference statements)
5
72
0
5
Order By: Relevance
“…Recent studies have noted the roles of keratinocytes in the pathogenesis of keloids [29,30]. Hahn et al demonstrated that keloid keratinocytes exhibit adhesion abnormalities and display a transcriptional signature reminiscent of cells undergoing epithelial-mesenchymal transition (EMT).…”
Section: Suzawa Et Al Revealed That Tranilast Selective Inhibition Omentioning
confidence: 99%
“…Recent studies have noted the roles of keratinocytes in the pathogenesis of keloids [29,30]. Hahn et al demonstrated that keloid keratinocytes exhibit adhesion abnormalities and display a transcriptional signature reminiscent of cells undergoing epithelial-mesenchymal transition (EMT).…”
Section: Suzawa Et Al Revealed That Tranilast Selective Inhibition Omentioning
confidence: 99%
“…This is why most studies on keloids focus on dermis and few on epidermis [4,17]. However, recent studies describe the epidermis of keloids as thickened, primarily due to hyperproliferation [4,7,17] and altered terminal differentiation [18] of keratinocytes,; some of them, indicating that keratinocytes also participate in the regulation of fibroblasts activity and might contribute to keloid pathogenesis [4,7,19]. On the other hand, several studies consider genetic predisposition as an important factor in the keloid formation and progression [2,5,9,20] whilst others deem the role of local mechanical Hematoxylin staining (H&E) from a biopsy of keloid showing reduced rete ridges, epidermal thickening, hyperkeratosis and spongiosis.…”
mentioning
confidence: 99%
“…frequently occur on the anterior portion of the chest, shoulders, upper back, arms, cheeks and earlobes [1,2,[5][6][7][8][9][10]. Histopathologically, keloids are defined as inflammatory disorders characterized by exhibiting a thickened dermis containing numerous fibroblasts, abnormal vascularization, increased inflammatory immune cells, abundant hyalinised collagen bundles (keloidal collagen) and extracellular matrix (ECM) components including collagen, elastin, fibronectin and proteoglycans such as syndecan and versican, mainly produced by activated fibroblasts [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
mentioning
confidence: 99%
See 2 more Smart Citations